2017
DOI: 10.1080/19338244.2017.1342588
|View full text |Cite
|
Sign up to set email alerts
|

Farmworker and nonfarmworker Latino immigrant men in North Carolina have high levels of specific pesticide urinary metabolites

Abstract: This paper compares detections and concentrations of specific organophosphate, bis-dithiocarbamate, and pyrethroid insecticide urinary metabolites among Latino male farmworkers and non-farmworkers in North Carolina. Data are from interviews and urine samples collected in 2012 and 2013. Farmworkers and non-farmworkers frequently had detections for OP and pyrethroid pesticide urinary metabolites. Detections of bis-dithiocarbamate urinary metabolites were less frequent, but substantial among the non-farmworkers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 22 publications
(23 reference statements)
3
11
2
Order By: Relevance
“…To the best of our knowledge, no other study has evaluated the urine concentrations of pyrethroid metabolites in a migrant Mexican population. In comparison to studies outside of Sonora, urinary concentrations of 3PBA were higher than the results obtained from the North Carolina studies by Raymer et al [41] and Arcury et al [38] as well as those reported by Panawet et al [38] in Thailand and a study conducted by Handal et al [40] in Ecuador with rose-workers (Table 5). Meanwhile, urinary concentrations for 4F3PBA and t-DCCA in our exploratory study were higher than the results reported by Handal et al [40] in Ecuador, but they were not reported in the other farmworker studies [38,39,41] (Table 5).…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…To the best of our knowledge, no other study has evaluated the urine concentrations of pyrethroid metabolites in a migrant Mexican population. In comparison to studies outside of Sonora, urinary concentrations of 3PBA were higher than the results obtained from the North Carolina studies by Raymer et al [41] and Arcury et al [38] as well as those reported by Panawet et al [38] in Thailand and a study conducted by Handal et al [40] in Ecuador with rose-workers (Table 5). Meanwhile, urinary concentrations for 4F3PBA and t-DCCA in our exploratory study were higher than the results reported by Handal et al [40] in Ecuador, but they were not reported in the other farmworker studies [38,39,41] (Table 5).…”
Section: Discussioncontrasting
confidence: 59%
“…However, Aldana-Madrid et al [32] studied local field workers from Sonora, which are not representative of our study population, that frequently migrate from the Southern Mexican States and temporarily reside in migrant dormitories located within the farm where they are employed. Interestingly, when comparing our OP results with other farmworker pesticide studies outside of the Sonora region, we found that concentrations of the chlorpyrifos metabolite (TCPY) in our study participants were higher than those reported in studies conducted in Ecuador, Thailand, and a study conducted in Latino farmworkers from North Carolina [38,39,41]. In addition, similar TCPY concentrations were reported in another study from North Carolina in male migrant tobacco workers who did not participate in any pesticide application processes [41].…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…The percentage of Latina farmworkers and non-farmworkers in this analysis with pesticide urinary metabolite detections and the concentrations of these metabolites are similar to those reported for male farmworkers and non-farmworkers in companion analyses. 4,5 Like this study, there were limited differences in detections and concentrations between male farmworkers and non-farmworkers in the companion analyses. Also like the results for male farmworkers and non-farmworkers in companion analyses, 4,5 detections and concentrations for each pesticide urinary metabolite differed between 2012 and 2013.…”
Section: Discussionmentioning
confidence: 58%
“…Most research on farmworkers has focused on men and migrant farmworkers. While some studies have focused explicitly on women (Arcury et al 2014; Arcury et al 2018a,2018b; Block 2014; Carney 2015; Golichenko and Sarang 2013; Meierotto and Som Castellano 2019a; Meierotto and Som Castellano 2019b; Quandt et al 2020), most research does not consider the intersection of gender and structural violence. In the discussion below, we provide a space for women to describe, in their own words, ways in which geography, gender, and immigration status intersect at multiple levels to increase isolation.…”
Section: Fod and Structural Violencementioning
confidence: 99%